Enteropathogenic Bacteria from Padang Food in Jatinangor SeptemberâOctober 2012 - Husain, Syed Anwar; Sudigdoadi, Sunarjati; Firmansyah W., Abdullah (Althea Medical Journal, 2015)
Background: Diarrhea is a food borne disease and still a major health problem in Indonesia. Padang foodis a popular cuisine and is exposed on an opened display, sometimes for many hours in room temperature,catering favorable conditions for bacterial growth. This study is undertaken to identify enteropathogenicbacteria on food in Padang restaurants located in Jatinangor, SumedangMethods: A laboratory study was conducted in the microbiology laboratory of the Department ofMicrobiology in the Faculty of Medicine, Universitas Padjadjaran, during SeptemberâOctober 2012. Sampleswere collected from 5 Padang restaurants located in Jatinangor using systematic random sampling. Fromeach restaurant, 4 wet samples were collected approximately 2â4 hours after being left open on the displayÂ shelves from sambal hijau, sambal merah, gulai babat and gulai nangka, cultured in tryptic soy broth (TSB)Â and incubated for 24 hours at 37 ÂºC, then inoculated in Mac Conkey agar and incubated for 24 hours at 37 ÂºC.Â Gram-staining was performed to identify gram-negative rods. The bacteria were put through biochemicalÂ tests.Results: Four species bacteria from the Enterobacteriaceae family were identified. The most frequentÂ bacteria which was identified in the samples was Shigella sp (4 from 20), followed by Klebsiella pneumonia(3 from 20), Escherichia coli and Pseudomonas sp were less identified.Conclusions: Various Padang foods have potential risks of bacterial contamination due to the preparation,handling, and serving. It should be considered that the prepared food should be covered and placed in foodwarmers, ensuring warm food for hours.Â [AMJ.2015;2(1):241â44]